2021
DOI: 10.1073/pnas.2016730118
|View full text |Cite
|
Sign up to set email alerts
|

A conformational switch driven by phosphorylation regulates the activity of the evolutionarily conserved SNARE Ykt6

Abstract: Ykt6 is a soluble N-ethylmaleimide sensitive factor activating protein receptor (SNARE) critically involved in diverse vesicular fusion pathways. While most SNAREs rely on transmembrane domains for their activity, Ykt6 dynamically cycles between the cytosol and membrane-bound compartments where it is active. The mechanism that regulates these transitions and allows Ykt6 to achieve specificity toward vesicular pathways is unknown. Using a Parkinson’s disease (PD) model, we found that Ykt6 is phosphorylated at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The second study examines serine 174 of YKT6 (serine 176 in the yeast orthologue Ykt6). Specifically, the authors also demonstrate that this residue must be phosphorylated in order for YKT6 to switch from a closed, cytosolic form to an open, membrane-bound form (McGrath et al, 2021). They show that this phosphorylation occurs in response to Ca 2+ signalling and is required for the role of YKT6 in trafficking along the secretory pathway, from the ER and Golgi, in human cells.…”
Section: Snare Regulation Through Phosphorylationmentioning
confidence: 86%
See 1 more Smart Citation
“…The second study examines serine 174 of YKT6 (serine 176 in the yeast orthologue Ykt6). Specifically, the authors also demonstrate that this residue must be phosphorylated in order for YKT6 to switch from a closed, cytosolic form to an open, membrane-bound form (McGrath et al, 2021). They show that this phosphorylation occurs in response to Ca 2+ signalling and is required for the role of YKT6 in trafficking along the secretory pathway, from the ER and Golgi, in human cells.…”
Section: Snare Regulation Through Phosphorylationmentioning
confidence: 86%
“…Two recent studies have identified conserved phosphorylation events on the R-SNARE YKT6 (Pradhipa Karuna et al, 2020;McGrath et al, 2021). YKT6 is an unusual SNARE, because it is extensively regulated through palmitoylation, geranylgeranylation and farnesylation.…”
Section: Snare Regulation Through Phosphorylationmentioning
confidence: 99%
“…There may be regulation at the level of mediator release by the soluble NSF attachment protein family as different members have roles in packaging, intracellular trafficking, and extracellular secretion of cytokines and chemokines [ 40 ]. A precedent has been published showing calcineurin is crucial in exocytotic processes through interactions with soluble NSF attachment family members [ 41 , 42 ], with the latter implicated in release of mediators by activated MCs.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Ykt6 modulates its interactions in a Parkinson's disease model, suggesting a potential involvement of this longin also in PD [129]. Indeed, Parkinson's disease α-synuclein perturbs the physiological response to lysosomal stress by impeding Ykt6 [130].…”
Section: Snare and Tethering Factorsmentioning
confidence: 99%